The contribution of Arthur Peacocke to the science-theology debate - Du Toit, Cornel W. (Skrif en Kerk, 1997)
The work of Arthur Peacocke may be considered to be a good example of the effort to link the findings and theories of new cosmology to the world of theology and religious thinking in a consistent and credible way. Highlights of Peacocke's theology pertaining to this venture are discussed. Some of the issues that are dealt with include his anti-reductionist approach, his critical realist stand, and his use of metaphor. Attention is also given to God's interaction with the world, the interaction of law and chance, God's self-limited omnipotence and omniscience, God and time, the suffering of creation and kenosis. The article concludes with some critical questions posed to Peacocke.
Free